2019
DOI: 10.1002/pen.25286
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Smoke Suppressants with APP for Enhancing the Flame Retardancy and Smoke Suppression on Vinyl Ester Resin

Abstract: Flame retarded and smoke suppressed vinyl ester resin (VER) were prepared through ammonium polyphosphate (APP) coupled with different smoke suppressants. The flame retardancy of these composites was tested by the limiting oxygen index and UL-94 tests. The typical combustion parameters including heat release rate (HRR), peak of HRR (p-HRR), total heat release, smoke production rate, and total smoke production were detected using a cone calorimeter. The smoke suppressants CaCO 3 , ZnMoO 4 , Cu 2 O, and Fe 2 O 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 42 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Besides, the new peaks at 963 and 929 cm −1 attributed to NH 3 are observed in the FTIR of RUPF with flame retardants. [ 29 ] The peaks originate from the degradation of APP. The release of NH 3 is beneficial to diluting the concentration of combustible pyrolysis volatiles in gas phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the new peaks at 963 and 929 cm −1 attributed to NH 3 are observed in the FTIR of RUPF with flame retardants. [ 29 ] The peaks originate from the degradation of APP. The release of NH 3 is beneficial to diluting the concentration of combustible pyrolysis volatiles in gas phase.…”
Section: Resultsmentioning
confidence: 99%
“…The higher residues of RPUF‐1 are attributed that polyphosphoric acid deriving from the degradation of APP reacts with the hydroxyl in PEPA, which forms the protective char residues. [ 29 ] Meanwhile, the residues of RPUF‐2 system and RPUF‐3 system are also improved. The results suggest that APP and PEPA, APP and PCP, APP and ADP system can improve the residues of RPUF composites.…”
Section: Resultsmentioning
confidence: 99%
“…In general, these materials display low toxicity and good flame retardant efficiency. They function by promoting a char layer at the surface of the polymer [ 8 , 9 ]. This char layer serves as an insulation barrier to inhibit heat feedback from the combustion zone and limit the formation of volatile fuel fragments.…”
Section: Introductionmentioning
confidence: 99%
“…And the interaction of the three additives through chemical reaction can heighten the thermal stability and strength of the char. Zhang et al [ 42 ] reported that CaCO 3 and APP showed effective synergistic action on decreasing the HRR and smoke release rate of vinyl ester resin. With the addition of 5 wt% CaCO 3 and 20 wt% APP, the LOI value and UL-94 result of the VE composites were 28.6 and V-0, which is attributed to the formation of continuous and dense char layer.…”
Section: Introductionmentioning
confidence: 99%